Antibiotic Resistance-Susceptibility Profiles of Streptococcus thermophilus Isolated from Raw Milk and Genome Analysis of the Genetic Basis of Acquired Resistances - Flórez, Ana B.; Mayo, Baltasar (Frontiers in Microbiology, 2017)
The food chain is thought to play an important role in the transmission of antibiotic resistances from commensal and beneficial bacteria to pathogens. Streptococcus thermophilus is a lactic acid bacterium of major importance as a starter for the dairy industry. This study reports the minimum inhibitory concentration (MIC) of 16 representative antimicrobial agents to 41 isolates of S. thermophilus derived from raw milk. Strains showing resistance to tetracycline (seven), erythromycin and clindamycin (two), and streptomycin and neomycin (one) were found. PCR amplification identified tet(S) in all the tetracycline-resistant strains, and ermB in the two erythromycin/clindamycin-resistant strains. Hybridisation experiments suggested each resistance gene to be located in the chromosome with a similar genetic organisation. Five antibiotic-resistant strains -two resistant to tetracycline (St-2 and St-9), two resistant to erythromycin/clindamycin (St-5 and St-6), and one resistant to streptomycin/neomycin (St-10)- were subjected to genome sequencing and analysis. The tet(S) gene was identified in small contigs of 3.2 and 3.7 kbp in St-2 and St-9, respectively, flanked by truncated copies of insertion sequence (IS) elements. Similarly, ermB in St-6 and St-5 was found in contigs of 1.6 and 28.1 kbp, respectively. Sequence analysis and comparison of the largest contig showed it to contain three segments (21.9, 3.7, and 1.4 kbp long) highly homologous to non-collinear sequences of pRE25 from Enterococcus faecalis. These segments contained the ermB gene, a transference module with an origin of transfer (oriT) plus 15 open reading frames encoding proteins involved in conjugation, and modules for plasmid replication and segregation. Homologous stretches were separated by short, IS-related sequences, resembling the genetic organisation of the integrative and conjugative elements (ICEs) found in Streptococcus species. No gene known to provide aminoglycoside resistance was seen in St-10. Four strain-specific amino acid substitutions in the RsmG methyltransferase were scored in this strain; these might be associated to its streptomycin/neomycin resistance. Under yoghurt manufacturing and storage conditions, no transfer of either tet(S) or ermB from S. thermophilus to L. delbrueckii was detected. The present results contribute towards characterisation of the antibiotic resistance profiles in S. thermophilus, provide evidence for the genetic basis of atypical resistances and deepen